An overview on the offshore emergency response planning in Malaysia - Shaluf, Ibrahim Mohamed; Ahmadun, Fakhru'l-Razi (Emerald Group Publishing, 2008)
Purpose: The purpose of this paper is to provide some definition and foundation principles regarding emergency and emergency management and to give an overview on the emergency response effectiveness at an offshore installation in Malaysia. Design/methodology/approach: The primary approach used is retrieval of the archived historical complex B emergency drills exercise records from 1997 to 1999. Retrieval of the historical records was made aimed at establishing a baseline information on the level of compliance with the required standards on emergency drills exercise of all the exercise conducted in the complex B for the three years. The secondary data required to complement the primary data are the level of competency gained by the complex B platform personnel as a result of their participation in their platform emergency drills exercise. A questionnaire survey was conducted where the objective of the survey was to map out the sample of general attitude profile and knowledge competency. Findings: The emergency drills on the Baram B complex are only partially adequate in nurturing effective emergency response preparedness. To achieve completeness and effective emergency drills performed as a conditioning process for an emergency response, the human resources knowledge and competency must be maintained and continuously enhanced. Continuous review for improvement purposes is required. The continuous improvement process should be parallel, covering both human resources and physical infrastructure. Originality/value: This paper presents an overview on the emergency response effectiveness at a complex B offshore platform. Benefits can be gained from the Malaysian experience.